New‐onset atrial fibrillation in the intensive care unit: Protocol for an international inception cohort study (AFIB‐ICU). Issue 6 (23rd April 2021) - Wetterslev, Mik; Møller, Morten Hylander; Granholm, Anders; Haase, Nicolai; Hassager, Christian; Lange, Theis; Hästbacka, Johanna; Wilkman, Erika; Myatra, Sheila Nainan; Shen, Jiawei; An, Youzhong; Siegemund, Martin; et al.
Abstract: Introduction: New‐onset atrial fibrillation (NOAF) is frequently observed in critically ill patients and may be associated with prolonged hospital stay and increased mortality. Considerable variation exists in the reported frequencies of NOAF due to the lack of a standardised definition and detection method. Importantly, there are limited data on NOAF in the intensive care unit (ICU). Thus, we aim to provide contemporary epidemiological data on NOAF in the ICU. Methods and Analysis: We have designed an international inception cohort study including at least 1, 000 consecutive adult patients acutely admitted to the ICU without prior history of persistent or permanent AF. We will present data on the incidence, risk factors, used management strategies and outcomes of NOAF. We will register data daily during stay in the ICU for a maximum of 90 days after admission. The incidence of NOAF and management strategies used will be presented descriptively, and we will use Cox regression analyses including competing risk analyses to assess risk factors for NOAF and any association with 90‐day mortality. Conclusion: The outlined international AFIB‐ICU inception cohort study will provide contemporary data on the incidence, risk factors, used management strategies and outcomes of NOAF in adult ICU patients. Ethics and dissemination: This observational study poses no risk to the included patients. All participating sites will obtain relevant approvals according to national laws before patient enrollment. Funding sources will have no influence on data handling, analyses or writing of the manuscript. The study report(s) will be submitted to an international peer‐reviewed journal.